EPIDEMIOLOGY OF DENGUE HEMORRHAGIC FEVER (DHF) IN SEMANU II PRIMARY HEALTH CENTRE, GUNUNGKIDUL FROM JANUARY-JUNE 2019 - Anggraini, Vidya Aries; Sulistyawati, Sulistyawati; Purnamawati, Desita; Wijayanti, Siwi Mars Pramatama (Epidemiology and Society Health Review (ESHR), 2020)
Background: Dengue Hemorrhagic Fever (DHF) is a public health problem in Indonesia. The dengue virus causes the disease through mosquito Aedes aegypti bite. This study aims to describe Dengue Hemorrhagic Fever (DHF) in Semanu II Primary Health Centre, GunungKidul, Yogyakarta.Methods: This is a quantitative study with a descriptive approach, describing DHF based variable person, place, and time, using secondary data. Data collection was carried out in August 2019 from secondary data reports SP2TP UPT PuskesmasSemanu II period January-June 2019.Results: Dengue Hemorrhagic Fever (DHF), which occurred in the region of Primary Health Center Semanu II in 2019, was a total of 18 cases with Incidence Rate 72/100,000 population. The majority of cases were found in the age group 6-11 years. 67% of the cases occurred in males. 72% of the cases happened in Pacarejo village. Most of the DHF incidence occurred in March (39%).Â Conclusions: The incidence of Dengue Hemorrhagic Fever in Primary Health Care Semanu II, most occurred in Pacarejo village, the majority in the age group 6-11 years. Male were the most infected group. And the highest DHF incidence occurred in March 2019